The coordination of upper and lower limb movements in shooting basketball from various distance: a pilot study - Feng, Z.; Chen, B.; Song, Y.; Zhu, Q. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
Using continuous relative phase (CRP) to quantify upper-lower limb coordination in shooting basketball. Six male participants performed free-throws and 3-point shots in a random order to yield 10 swish shots and 10 missed shots at each distance for analysis. The SPM analysis on CRPs revealed that a similar strategy was used to coordinate upper and lower limbs for shooting (p>0.05), with no distinguished coordination pattern for swish shots (p>0.05). The analysis on between-trial variability of coordination revealed that swish shots required more adjustment of proximal coordination, and 3-point shots entailed more adjustment of distal coordination. These findings shed light on a better understanding of limb coordination required before ball release in shooting basketball.